2020 12th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP) 2020
DOI: 10.1109/csndsp49049.2020.9249515
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Interface Bonding Schemes for VLC with Mobility and Shadowing

Abstract: Node mobility and shadowing are the most common reasons requiring a handover in vehicular visible light communications (VVLC). In order to provide seamless mobility during the handover, it is required to decrease the network outage duration. This paper aims to improve the outage duration in handover caused by mobility and shadow for VLC networks. We analyze interface bonding schemes using two different primary interface reselection methods. The results show that using "failure" interface selection method inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The transmission techniques commonly used in VLC systems include the User Datagram Protocol (UDP) [29,30], and on/off keying (OOK) [31,32], using an arbitrary waveform generator or universal software radio peripheral (USRP) devices (National Instruments, Austin, TX, USA). In our paper, V2V VLC is achieved using OOK, where an LED is employed as the light source for data transmission, and data are carried when the LED is either on or off.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The transmission techniques commonly used in VLC systems include the User Datagram Protocol (UDP) [29,30], and on/off keying (OOK) [31,32], using an arbitrary waveform generator or universal software radio peripheral (USRP) devices (National Instruments, Austin, TX, USA). In our paper, V2V VLC is achieved using OOK, where an LED is employed as the light source for data transmission, and data are carried when the LED is either on or off.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A growing number of research works on the handover in VLC and wireless mobile networks have been reported in the literature, which are mostly focused on proposing schemes to achieve a smooth handover with decreasing data rate fluctuation and increasing transmission bandwidth [10], [12]. In addition, in [8], [16] and [17], we proposed and evaluated new architectural designs, aiming at handover delay decrement and VLC network throughput increment.…”
Section: Related Workmentioning
confidence: 99%
“…Note that to the best of authors knowledge this paper is the first to evaluate T hod in a V-VLC network with two dimensions movements, considering possible scenarios where an AGV experiences link failure during handover. Previously, in [16] and [8], we initially proposed the idea of using link aggregation on top of multiple VLC clients for AGV and frequency division for neighboring LAPs and their corresponding LCs. In addition, we analyzed an interface bonding scheme using only two different primary interfaces and evaluated T hod for the AGV with a linear movement [8], [16].…”
Section: B Comparison To the State Of The Artmentioning
confidence: 99%
“…Additionally, mobile terminals in the factory will face frequent handovers [7,8] between high-density access points. In order to ensure that the voice and data communications are not interrupted in the mobile scenario, the handover needs to be performed so that the user can access the LAP which can provide better communication service quality [9][10][11][12]. In this case, the handover cannot be simply based on the method under the plane receiver, but should combine the characteristics of the cubic receiver under study.…”
Section: Introductionmentioning
confidence: 99%